Perbandingan Iluminasi dan Brightness dengan Metode Pengukuran - Amir Hamzah Pohan; Bintang Unggul Prawirawan (Universitas Muhammadiyah Tangerang, 2022)
All activities require lighting, in order to produce quality, efficient, effective, fast and safe results, including learning and teaching activities. If the intensity of lighting is outside the current standard, 250-500 lux (other references are 30-50 fc), or about 402.78 lux, then the teaching and learning performance is not optimal, the atmosphere is not supportive, students cannot concentrate fully, it is difficult and slow grasp the meaning of the lesson. So this paper describes the research on the intensity of lighting in schools2, using survey methods and questionnaires. The goal is to obtain information data about the intensity of lighting in schools, whether it is in accordance with existing standards. The result is about 409.4417 lux, higher than the previous standard. This can indicate, among other things, the decline in eye power of the current generation. In addition, with this finding, further corrective actions can be carried out quickly and precisely.